Erigindo Germânico: Domiciano e seu programa construtor em Roma a partir da retórica laudatória de Estácio (81-96) - Baptista, Natan Henrique Taveira (2021)
This study interprets the political-literary mobilization of the building program of Titus Flavius Domitianus in Rome, between the years of 81 and 96, through the poetry of Publius Papinius Statius — Thebaid, Achilleid, and, particularly, Siluae. It correlates, therefore, the discursive representations about the monumental architecture landscape built in verse by the poet to the self-expression of the princeps in his building project and, consequently, to the politicalideological system of the Principate. Because of this, the dissertation correlates Statius, Domitian, and his building program through the encomium, arguing for the convergence between the three poles of the equation — laudans, laudatus, laus (who praises, who is praised, the praise) — with implications for the social position of the first, the political expression of the second, and the monumental representation of the latter during the erratic historical context of the last two decades of the first century CE. This work is theoretically inserted in Discourse Studies, by proposing that, in the poems, the economy of symbolic exchanges is processed, which gives space intelligibility and legitimizes, concomitantly, the prince’s power and the poet’s authority. To harmonize with the theoretical option and with the documental body, the textual examination of Discourse Analysis, as proposed by the Russian-French school, is used, also from the considerations of rhetorical-poetic hermeneutics. The dissertation investigates, in light of the above, the ways of presenting and signifying public monuments in the imperial capital, mainly the equestrian statue, the Domitianic forum and its temple of Janus, the temple of the gens Flavia, the palace, and the Flavian Amphitheater through dialogue between Statian poetry and the critical fortune of archaeological discoveries. It recognizes that Statius, at the socio-political level, uses praise for the spatial dimension as an argumentative and persuasive resource. Through rhetoric, he establishes his authority and his social position, as well as builds an éthos that expands his ties of amicitia and his access to the imperial circle. As a consequence, the poet strengthens the didactic power of his work and his function as guardian of memory, which together contribute to the status of epic canon during the Domitianic age. The study concludes that there is a political-literary alliance between power and poetry that, through praise, symbolically supports and legitimizes the interpretation conveyed by the architecture of the last Flavian, based on a discourse of military triumphalism, civic consensus, and restoration of social order. To ensure such construction of balance and stability, both emperor and poet supplied their monuments from the Julio-Claudian building paradigm.